A molecular basis for water motion detection by the mechanosensory lateral line of zebrafish. Issue 1 (December 2017) - Chou, Shih-Wei; Chen, Zongwei; Zhu, Shaoyuan; Davis, Robin; Hu, Jiaqi; Liu, Li; Fernando, Carol; Kindig, Kayla; Brown, William; Stepanyan, Ruben; McDermott, Brian
Abstract Detection of water motion by the lateral line relies on mechanotransduction complexes at stereocilia tips. This sensory system is comprised of neuromasts, patches of hair cells with stereociliary bundles arranged with morphological mirror symmetry that are mechanically responsive to two opposing directions. Here, we find that transmembrane channel-like 2b (Tmc2b) is differentially required for mechanotransduction in the zebrafish lateral line. Despite similarities in neuromast hair cell morphology, three classes of these cells can be distinguished by their Tmc2b reliance. We map mechanosensitivity along the lateral line using imaging and electrophysiology to determine that a hair cell's Tmc2b dependence is governed by neuromast topological position and hair bundle orientation. Overall, water flow is detected by molecular machinery that can vary between hair cells of different neuromasts. Moreover, hair cells within the same neuromast can break morphologic symmetry of the sensory organ at the stereocilia tips. In fish, water motion is detected by mechanosensitive hair cells located in the lateral line. Here the authors show that the molecular machinery for mechanotransduction, including transmembrane channel-like 2b (Tmc2b), varies depending on both hair cell location and hair bundle orientation.